3D printing-assisted interphase engineering of polymer composites: Concept and feasibility - G. Szebenyi; T. Czigany; B. Magyar; J. Karger-Kocsis (eXPRESS Polymer Letters)
We introduced a general concept to create smart, (multi)functional interphases in polymer composites with layered reinforcements, making use of 3D printing. The concept can be adapted for both thermoplastic and thermoset matrix-based composites with either thermoplastic- or thermoset-enriched interphases. We showed feasibility using an example of a composite containing a thermoset matrix/thermoplastic interphase. Carbon fiber unidirectional reinforcing layers were patterned with poly(ε-caprolactone) (PCL) through 3D printing, then infiltrated with an amine-cured epoxy (EP). The corresponding composites were subjected to static and dynamic flexure tests. The PCL-rich interphase markedly improved the ductility in static tests without deteriorating the flexural properties. Its effect was marginal in Charpy impact tests, which can be explained with effects of specimen and PCL pattern sizes. The PCL-rich interphase ensured self-healing when triggered by heat treatment above the melting temperature of PCL.